Financial Openness and Capital Inflows to Emerging Markets : In Search of Robust Evidence - Cerdeiro, Diego (IMF Working Papers; Working Paper ;, 2019)
We reassess the connection between capital account openness and capital flows in an empirical framework that is grounded in theory and makes use of previously unexplored variation in the data. We demonstrate how our theory-consistent regressions may overcome some ubiquitous measurement problems in the literature by relying on interaction terms between financial openness and traditional push-pull factors. Within our proposed framework, we ask: what can be said robustly about the effect of capital account restrictions on capital flows? Our results warrant against over-interpreting the existing cross-country evidence as we find very few robust relationships between capital account restrictiveness and various types of capital inflows. Countries with a higher degree of financial openness are more susceptible to some, but by no means all, push and pull factors. Overall, the results are still consistent with a complex set of tradeoffs faced by policymakers, where the ability to shield the domestic economy from volatile capital flow cycles must be weighed against the sources of exogenous risks and potential long run growth effects.